Microstructure Investigation of the Spark Plasma Sintered Cu—Al—Ni Shape Memory Material - Monastyrsky, G.E.; Kotko, A.V.; Gilchuk, A.V.; Ochin, P.; Kolomytsev, V.I.; Koval, Yu.N. (Металлофизика и новейшие технологии, 2014)
Исследована микроструктура компактов Cu—13,0Al—3,9Ni—0,4Ti—0,2Cr масс.%, спечённых плазменно-искровым методом из электроэрозионных порошков, изготовленных из мастер-сплава в жидком аргоне. Досліджено мікроструктуру компактів Cu—13,0Al—3,9Ni—0,4Ti—0,2Cr ваг.% спечених плазмово-іскровим методом із електроерозійних порошків, виготовлених із мастер-стопу в рідкому арґоні. The microstructure of Cu—13.0Al—3.9Ni—0.4Ti—0.2Cr wt.% compacts sintered by spark plasma method from powders prepared by spark-erosion method in liquid argon from master alloy is investigated.